Learning to control tissue damage while fighting Aspergillus - Wong, Alicia Yoke Wei; Fric, Jan; Zelante, Teresa (Medical mycology, 2019)
Aspergillus moulds are increasingly being recognised as significant human pathogens that can cause life-threatening infections in the context of host immune dysregulation, particularly in the lung. It is now clear that there is a close relationship between infection susceptibility and the fine regulation of pulmonary immunity and inflammation. While the contribution of IL-17/Th17 responses to both physiological and pathological lung inflammation is now well established, the cellular interactions, soluble factors, and signalling pathways that determine Th17 cell responses to fungal infection remain unclear. Here, we identify potential key mediators of fungus-DC-T cell interactions in the respiratory tract, with a focus on the DC-derived cytokines thought to exert a major influence on generation of pathological Th17 cells. We review recent data indicating a crucial role for Aspergillus-induced autophagy in lung DCs on subsequent T-cell polarization and modulation of 'stemness', which appears critical for avoiding pathological lung inflammation and promoting disease resolution.
Keywords: Autophagy; zvířata; dendritické buňky; cytokiny; IL-2; Dendritic Cells; Aspergillus; Animals; autofagie; Cytokines; Disease Models, Animal; Pulmonary Aspergillosis; buňky Th17; modely nemocí na zvířatech; plicní aspergilóza; lidé; Humans; Host-Pathogen Interactions; Th17 Cells; Inflammation; Th17; interakce hostitele a patogenu